OnabotulinumtoxinA for the treatment of major depressive disorder: a phase 2 randomized, double-blind, placebo-controlled trial in adult females. (January 2020) - Brin, Mitchell F.; Durgam, Suresh; Lum, Arlene; James, Lynn; Liu, Jeen; Thase, Michael E.; Szegedi, Armin
Abstract : This 24-week double-blind placebo-controlled multicenter randomized phase 2 trial evaluated efficacy and safety of onabotulinumtoxinA (onabotA; BOTOX) vs. placebo for major depressive disorder (MDD) [NCT02116361]. Primary endpoint was the change in Montgomery-Åsberg Depression Rating Scale (MADRS); secondary endpoints were Clinical Global Impressions-Severity and 17-item Hamilton Depression Rating Scale at week 6. A total of 255 adult females were treated. OnabotA 30 U approached significance compared to placebo on MADRS (mixed-effect model repeated measures least-squares mean difference: −3.7; P = 0.053) and reached significance [least-squares mean differences: −3.6 to −4.2; P < 0.05 (two-sided)] at weeks 3 and 9. Secondary endpoints were also significant at several time points. At week 6, onabotA 50 U did not separate from placebo in any parameters. OnabotA was generally well-tolerated: the only treatment-emergent adverse events reported in ≥5% in either onabotA group, and more than matching placebo were headache, upper respiratory infection, and eyelid ptosis. OnabotA 30 U, administered in a standardized injection pattern in a single session, had a consistent efficacy signal across multiple depression symptom scales for 12 or more weeks. OnabotA 30 U/placebo MADRS differences of (observed ANCOVA) ≥4.0 points (up to week 15) and ≥2.0 points (weeks 18–24) agree with the 2-point change threshold considered clinically relevant in MDD. OnabotA is a local therapy and is not commonly associated with systemic effects of conventional antidepressants and may represent a novel treatment option for MDD. Abstract : Supplemental Digital Content is available in the text.